Desenvolvimento de eletrocatalisadores de sulfeto de molibdênio para produção de hidrogênio via eletrólise da água - Silva, Marina Medina da (Universidade Federal de São Carlos, 2023)
The amorphous molybdenum sulfide, MoSx, has shown to be an excellent electrocatalyst for the hydrogen evolution reaction (HER) and can be synthesized by electrodeposition. In this study, the electrodeposition of MoSx on conductive FTO, Ti, TiO2 semiconductor in the form of film (TiO2) and nanotubes (TiO2 NT), and carbon paper (CP) substrates was investigated. The deposition conditions and the relationship between the structure, morphology, and composition of the prepared films with the electrocatalytic activity for HER were studied. The results showed that the metal substrate, in comparison with FTO, reduced the resistance at the substrate/catalyst interface, as the value for FTO was almost 8 times higher than the value for the Ti substrate. The ease of electrical transport between Ti-MoSx had an effect on the Tafel coefficient, decreasing the value from 110 mV dec-1 in MoSx/FTO to 75 mV dec-1 in MoSx/Ti. The higher electrocatalytic activity for HER of the MoSx/Ti electrode was also observed at the overpotential required to reach -10 mA cm-2 (10), as this electrode required 123 mV, while the value for MoSx/FTO was 262 mV. The deposition of MoSx on TiO2 NT affected the catalyst growth mechanism, altering the MoSx chemical composition. XPS analysis showed an increase in the atomic percentage of the most active site for HER (Sbridg), in which a value of 47% was observed for MoSx deposited on a TiO2 film, while for MoSx deposited on TiO2 NT, the percentage increased to 67%. This result was related to the decrease in the 10, in which MoSx/TiO2 required 190 mV, while the value for MoSx/TiO2 NT was only 93 mV. However, this electrode was not stable, possibly due to greater exposure to the breaking of S-S bonds after H adsorption. Deposition on CP was possible after treatment to increase substrate hydrophilicity. After analyzing the deposition conditions, the electrode was applied as a cathode in the PEM electrolyzer at the Jülich Forschungszentrum, proving to be active for the RDH and stable under the operating conditions in which it was evaluated. In summary, the study of the type of substrate used for MoSx electrodeposition was essential to increase the catalyst´ electrocatalytic activity for HER.
Development of molybdenum sulfide electrocatalyst for hydrogen production via water electrolysis
Keywords: Sulfeto de molibdênio amorfo; Amorphous molybdenum sulfide; Reação de desprendimento de hidrogênio; Hydrogen evolution reaction; Eletrólise da água; Water electrolysis; Eletrodeposição; Electrodeposition; Efeito do substrato; Substrate effect; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA